Brain neuroimaging of domestic cats: Correlation between computed tomography and cross- sectional anatomy - Nepomuceno, A. C.; Zanatta, R.; Chung, D. G. [UNESP]; Costa, P. F. [UNESP]; Feliciano, M. A.R. [UNESP]; Avante, M. L. [UNESP]; Lopes, L. S.; Canola, J. C. [UNESP] (FapUNIFESP (SciELO), 2016)
Computed tomography of the brain is necessary as part of the diagnosis of lesions of the central nervous system. In this study we used six domestic cats, male or female, aged between one and five years, evaluated by Computed Tomography (CT) examination without clinical signs of central nervous system disorders. Two euthanized animals stating a condition unrelated to the nervous system were incorporated into this study. The proposal consisted in establishing detailed anatomical description of tomographic images of normal brain of cats, using as reference anatomical images of cross sections of the stained brain and cranial part, with thicknesses similar to the planes of the CT images. CT examinations were performed with and without intravenous iodinated contrast media for live animals. With one euthanized animal, the brain was removed and immediately preserved in 10% formalin for later achievement in cross-sectional thickness of approximately 4mm and staining technique of Barnard, and Robert Brown. The head of another animal was disarticulated in the Atlanto-occipital region and frozen at -20°C then sliced to a thickness of about 5mm. The description of visualized anatomical structures using tomography is useful as a guide and allows transcribing with relative accuracy the brain region affected by an injury, and thus correlating it with the clinical symptoms of the patient, providing additional information and consequent improvement to veterinarians during the course of surgical clinic in this species.
Keywords: Brain anatomy; Feline; Tomography